Footballers’ endurance based on Berlin football teams - Kalinowski, Paweł; Kalinowska, Katarzyna; Jerszyński, Damian; Rachwalski, Krzysztof; Pietranis, Dariusz (Quality in Sport, 2020)
Endurance is one of the most essential motor skills in the well planned training process in football. The high intensity and pace of the game force the players to be very well prepared. The increasing requirements of the game over the years direct the attention towards the oxygen mechanisms of football players. The aim of the study was to determine a relationship between the endurance tested by the Cooper test and the effectiveness of the game, determined by a modified method of competent referees. The study was inclued 90 footballers of german clubs SV Berliner Brauereien, Berliner TSC and BSC Eintracht Südring Berlin. The results of studies conducted in Berlin in 2015-2018 were analysed. Descriptive statictics were conducted: mean (X), minimum values (min), maximum values (max) and standard deviation (SD). Normal distribution was checked and correlation coefficient were determined. The results of the study were statistically analyzed in Statistica 13,3. In the study on a bigger number of players, a statistically significant relationship was noted between the effectiveness of the game of German team players and cardio-respiratory endurance.